Development and assessment of GC/MS and HPAEC/PAD methodologies for the quantification of α-galacto-oligosaccharides (GOS) in dry beans (Phaseolus vulgaris). (1st July 2021) - Pico, Joana; Vidal, Natalia P.; Widjaja, Listiya; Falardeau, Louis; Albino, Lionel; Martinez, Mario M.
Highlights: HPAEC/PAD and GC/MS methods were compared for the analysis of GOS in beans. Stable trimethylsilyl derivatizations for GC/MS analysis were achieved for all GOS. GC/MS was chosen for quantifying GOS in bean with extraction efficiencies near 100%. Stachyose was the most abundant GOS in all the bean samples analyzed by GC/MS. Red Kidney presented the highest total GOS content among the six bean varieties. Abstract: The quantification of α-Galacto-oligosaccharides (GOS) in beans has been increasingly approached through different methodologies. However, reported GOS contents revealed up to 8-times disparity, which cannot be only attributed to the bean cultivar and underlines the need of using validated analytical methodologies. This study aimed to optimize and validate the extraction of the most abundant GOS found in beans, namely raffinose, stachyose and verbascose, and comparatively assess their determination by High-Performance Anion Exchange Chromatography/Pulsed Amperometric Detector (HPAEC/PAD) and Gas Chromatography/Mass Spectrometry (GC/MS). Hot sonication followed by shaking with 70% ethanol resulted in excellent GOS extraction efficiencies (92.54–107.94%). GC/MS determination was more reliable than HPAEC/PAD, with limits of quantification of 4.48–224.31 mg/kg and intra/inter-day repeatabilities <10%. The analysis of six bean varieties proved the feasibility of the GC/MS methodology, displaying total GOS contents from 1453.07 ± 169.31 to 2814.34 ± 95.28 mg/100 g. Stachyose was significantly (p < 0.05) the main GOS in all samples.